Analisis Pengaruh Leverage, Intensitas Modal, dan Ukuran Perusahaan terhadap Konservatisme Akuntansi pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek IndonesiaAnalisis Pengaruh Leverage, Intensitas Modal, dan Ukuran Perusahaan terhadap Konservatisme Akuntansi pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Wijaya, Haris Agung (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of leverage, capital intensity, and firm size on accounting conservatism in mining companies listed on the Indonesia Stock Exchange during the 2017–2021 period. The study employs a quantitative approach using secondary data obtained from annual financial statements. The sample was selected through purposive sampling and consisted of 19 companies, resulting in 95 firm-year observations. Accounting conservatism was measured using an accrual-based conservatism model, leverage was measured using the debt-to-assets ratio, capital intensity was measured using the ratio of net fixed assets to total assets, and firm size was measured using the logarithm of total assets. Data were analyzed using multiple linear regression with SPSS version 25. The results show that leverage has a negative but insignificant effect on accounting conservatism, capital intensity has a negative and significant effect, and firm size has a negative but insignificant effect. The coefficient of determination is 8.7%, indicating that the three independent variables explain 8.7% of the variation in accounting conservatism, while the remaining 91.3% is explained by other factors outside the research model.